USP15-dependent lysosomal pathway controls p53-R175H turnover in ovarian cancer cells - Achuth Padmanabhan (Nature Portfolio, 2018)
Gain-of-function mutants of p53 are important for cancer development and strategies to target specifically these isoforms are being investigated. Here the authors report that USP15 is a deubiquitinase specifically regulating p53-R175H levels that can be targeted by a small molecule.